2019
DOI: 10.1002/mnfr.201801380
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Quinolyl‐Substituted Analogue of Resveratrol Inhibits LPS‐Induced Inflammatory Responses in Microglial Cells by Blocking the NF‐κB/MAPK Signaling Pathways

Abstract: Scope The anti‐neuroinflammatory effect of a novel quinolyl‐substituted analogue of resveratrol (RV01) on lipopolysaccharide (LPS)‐induced microglial activation is investigated, as well as the possible underlying mechanisms. Methods and results Cell viability is measured using an MTT assay. Nitric oxide (NO) release is determined by nitrite assay. The interaction between RV01 and inducible nitric oxide synthase (iNOS) is studied using molecular docking. Free radical scavenging activity and reactive oxygen spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…MAPK pathways have been known to be involved in the induction of microglial proinflammatory factor production [48]. In agreement with the previous study [69], our results showed that LPS significantly increased the phosphorylation of ERK, p38, and JNK in the microglial cultures compared with the control cultures. SIS3 significantly induced the phosphorylation of ERK and p38, but not JNK, in the cultures.…”
Section: Discussionsupporting
confidence: 93%
“…MAPK pathways have been known to be involved in the induction of microglial proinflammatory factor production [48]. In agreement with the previous study [69], our results showed that LPS significantly increased the phosphorylation of ERK, p38, and JNK in the microglial cultures compared with the control cultures. SIS3 significantly induced the phosphorylation of ERK and p38, but not JNK, in the cultures.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, it has been reported that resveratrol preconditioning modulates inflammatory response of hippocampus after global cerebral ischemia in rat [29]. In addition, resveratrol has been documented to be able to suppress neuro-inflammation mediated by microglia, protect neurons from inflammatory damage, and relieve inflammation of the airway caused by asthma and airway remodeling [30,31].…”
Section: The Anti-inflammatory Activity Of Resveratrolmentioning
confidence: 99%
“…10 μM was used as the highest concentration of kellerin in our in vitro study according to our previous study (Xing et al, ). Cell viability was examined using the MTT assay as previously reported (Hou et al, ).…”
Section: Methodsmentioning
confidence: 99%